Multilaboratory approach to preclinical evaluation of vaccine immunogens for placental malaria - Fried, Michal (2013)
Pregnancy malaria is caused by Plasmodium falciparum-infected erythrocytes that adhere to the placental receptor chondroitin sulfate A (CSA) and sequester in the placenta; women become resistant to pregnancy malaria as they acquire antiadhesion antibodies that target surface proteins of placental parasites. VAR2CSA, a member of the P. falciparum EMP1 variant surface antigen family, is the leading candidate for a pregnancy malaria vaccine. Because VAR2CSA is a high-molecular-weight protein, a vaccine based on the full-length protein may not be feasible. An alternative approach has been to develop a vaccine targeting individual Duffy binding-like (DBL) domains. In this study, a consortium of laboratories under the Pregnancy Malaria Initiative compared the functional activity of antiadhesion antibodies elicited by different VAR2CSA domains and variants produced in prokaryotic and eukaryotic expression systems. Antisera were initially tested against laboratory lines of maternal parasites, and the most promising reagents were evaluated in the field against fresh placental parasite samples. Recombinant proteins expressed in Escherichia coli elicited antibody levels similar to those expressed in eukaryotic systems, as did the two allelic forms of the DBL4 and DBL5 domains. The procedures developed for this head-to-head comparison will be useful for future evaluation and down-selection of malaria vaccine immunogens.